HIGHLY EFFECTIVE LUNG DELIVERY OF A FULLY HUMAN MONOCLONAL ANTIBODY TARGETING PSEUDOMONAS AERUGINOSA FOLLOWING INTRA-NASAL ADMINISTRATION - AZMI ADAWI,; LEWIS F. NEVILLE, (International Journal of Pharma and Bio Sciences, 2013)
A time-course study was performed to assess lung concentrations and bioactivities of a fully human monoclonal antibody (mAb) targeting Pseudomonas aeruginosa (PA) flagella type b (LST-007) following intra-nasal administration. Intra-nasal administration of LST-007 (5 mg/kg) resulted in high mAb concentrations (11 mg/ml) within the bronchoalveolar lavage (BAL) fluid at 15 min post-administration, which decreased to 3 mg/ml at 4 hr. In marked contrast, LST-007 concentrations in blood were 110 and 11 fold lower at the same time points. Scrutinization of BAL fluid demonstrated the presence of both intact and immunoreactive LST-007 towards PAO1 bacteria, which impeded bacterial motility, underscoring the maintenance of biological activity. These compelling data lay credence that intra-nasal and thus potential inhalation modes of administration might represent bona fide routes for a targeted mAb delivery to the lung environment and establishment of therapeutically effective concentrations. Such delivery approaches could help combat life-threatening, pneumonia infections caused by PA.